Innovation of Evaluation of Plating Dance Learning for High School Students Based on “Find the Match” - Putri Ajeng Wulan Julitasari; Agus Cahyono; Syahrul Syah Sinaga; Wahyu Lestari (Universitas Muhammadiyah Enrekang, 2024)
Evaluation innovation in art learning using digital media is very necessary. In the era of digitalization development, teachers must have skills in designing and using innovative learning media to attract students' interest. Through evaluating learning innovations using the WorldWall